Sistem Informasi Geografis Daerah Rawan Banjir Untuk Wilayah Kota Medan - Sunaryo Winardi; Charles Charles; Steven Steven; Rizki Abdul Azis; Arwin Halim (Jurnal SIFO Mikroskil, 2019)
Flooding is as an event of the overflow of water from a river or drainage because unable to accommodate the amount of water flow. Medan is one area that is often flooded. GIS can be used to visualize the flood maps that are useful as disaster management and decision-making. GIS is used to enter, store, recall, process, analyze, and produce data on the condition of flood in geospatial of medan city based on websites. Web-based software built with the Waterfall method as a method of system development and system testing is performed using blackbox testing testing and using Likert scale to determine the calculation of the time scale given questionnaire. The result is a system capable of providing convenience to the user in finding areas (mapping) in the visualization of color QGIS flood area of Medan city and the developed system can help users with an index value of percentage of 66.67%.